Strategies to Build Trust and Recruit African American and Latino Community Residents for Health Research: A Cohort Study. Issue 5 (21st June 2015) - Sankaré, Ibrahima C.; Bross, Rachelle; Brown, Arleen F.; del Pino, Homero E.; Jones, Loretta F.; Morris, D'Ann M.; Porter, Courtney; Lucas‐Wright, Aziza; Vargas, Roberto; Forge, Nell; Norris, Keith C.; Kahn, Katherine L.
Abstract: Background: This study used Community Partnered Participatory Research (CPPR) to address low participation of racial and ethnic minorities in medical research and the lack of trust between underrepresented communities and researchers. Methods: Using a community and academic partnership in July 2012, residents of a South Los Angeles neighborhood were exposed to research recruitment strategies: referral by word‐of‐mouth, community agencies, direct marketing, and extant study participants. Results: Among 258 community members exposed to recruitment strategies, 79.8% completed the study. Exposed individuals identified their most important method for learning about the study as referral by study participants (39.8%), community agencies (30.6%), word‐of‐mouth (17.5%), or direct marketing promotion (12.1%). Study completion rates varied by recruitment method: referral by community agencies (88.7%), referral by participants (80.4%), direct marketing promotion (86.2%), word of mouth (64.3%). Conclusions: Although African American and Latino communities are often described as difficult to engage in research, we found high levels of research participation and completion when recruitment strategies emerged from the community itself. This suggests recruitment strategies based on CPPR principles represent an important opportunity for addressing health disparities and our high rates of research completion should provide optimism and a road map for next steps.